2015
DOI: 10.1016/j.athoracsur.2015.05.057
|View full text |Cite
|
Sign up to set email alerts
|

Beating-Heart Versus Conventional On-Pump Coronary Artery Bypass Grafting: A Meta-Analysis of Clinical Outcomes

Abstract: BH-ONCAB is a safe and comparable alternative to C-ONCAB in terms of early mortality and late survival. Furthermore, BH-ONCAB may confer a particular advantage in preventing perioperative myocardial infarction and reducing overall blood loss. Future work should focus on larger matched studies and multicenter randomized controlled trials that risk-stratify patients according to preoperative ventricular function and renal insufficiency to allow us to optimize our surgical revascularization strategy in these high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 18 publications
4
33
0
Order By: Relevance
“…The results showed that PAD-CAB allowed for a significantly higher number of bypass grafts performed with greater revascularization and statistically insignificant differences in mortality and major cardiovascular adverse events. Similar findings were reported the year before by the same authors [22,23]. The author's (LES) experience with beating heart surgery-both OP-CAB and PAD-CAB-was initially developed in response to the challenges associated with CABG surgery in sick patients with weak hearts.…”
Section: Discussionsupporting
confidence: 68%
“…The results showed that PAD-CAB allowed for a significantly higher number of bypass grafts performed with greater revascularization and statistically insignificant differences in mortality and major cardiovascular adverse events. Similar findings were reported the year before by the same authors [22,23]. The author's (LES) experience with beating heart surgery-both OP-CAB and PAD-CAB-was initially developed in response to the challenges associated with CABG surgery in sick patients with weak hearts.…”
Section: Discussionsupporting
confidence: 68%
“…As the main source of enhanced oxidative stress and inflammatory response during CABG seems to be ECC using, several studies evaluating influence of on and – off pump operation on outcome were performed and advantages of beating heart techniques was confirmed in terms of early mortality [48]. Providing of on – pump CABG was reported as a predictive factor of low cardiac output syndrome [49] and perioperative myocardial infarct [50], although the results of large randomized trials did not confirm the significant superiority off- pump technique [51]. Also in high operative risk patients treated preventively with intra – aortic balloon pump there was no significant difference in perioperative mortality in comparison with control group [52].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, as an alternative to both techniques, the on-pump beating-heart coronary artery bypass grafting (ONBHCAB) technique has gained acceptance in order to eliminate the harmful effects of cross-clamping, cardioplegia and unloading the heart, and it preserves both native coronary blood flow and cardiac output during surgery 5-7. Although a metaanalysis revealed better short-term outcomes and late survival rates following ONBHCAB compared with conventional CABG (CCAB),7 studies comparing the outcomes of ONBHCAB and OPCAB techniques in a similar patient population are lacking.…”
Section: Objectivesmentioning
confidence: 99%
“…Although a metaanalysis revealed better short-term outcomes and late survival rates following ONBHCAB compared with conventional CABG (CCAB),7 studies comparing the outcomes of ONBHCAB and OPCAB techniques in a similar patient population are lacking. Therefore we aimed to compare the short-term outcomes and long-term major adverse cardiovascular event (MACE)-free survival after ONBHCAB versus OPCAB in a matched population.…”
Section: Objectivesmentioning
confidence: 99%